Pengaruh Fanatisme, Self-control, dan Religiusitas terhadap Perilaku Agresi Verbal pada Mahasiswa Penggemar K-Pop di Kota Bandung - Muhamad Anshori; Wika Fitri Walriani; Zulmi Ramdani; Ivena Kemala Motik; Zahra Aulia Ramadhani; Delizza Oktaviani (Universitas Trunojoyo Madura, 2023)
Verbal aggression is rife among K-Pop fans who use social media to communicate. One of the things that causes verbal aggression behavior is the tendency of fanaticism due to excessive enthusiasm. In addition, excessive fanaticism makes a person deindividuated and unable to control himself. On the other hand, Indonesia is a country that applies religiosity as a guide for behavior. This study aims to determine the effect of fanaticism, self-control, and religiosity on verbal aggression behavior in K-Pop fan students in Bandung. The hypothesis in this study is that there is a significant influence either partially or simultaneously between fanaticism, self-control, and religiosity on verbal aggression. Subjects in this study amounted to 291 students with accidental sampling technique. The data analysis technique used is multiple regression analysis using SPSS 26 software. The results of this study indicate that there is a simultaneous influence of fanaticism, self-control, and religiosity on verbal aggression behavior with a contribution value of 41%, which suggests that the tendency of fanaticism is due to enthusiasm that controls excessive self-esteem, low self-control, and understanding of extrinsic religiosity through social media among diehard K-pop fans are significant factors in the occurrence of verbal aggression phenomena such as fan-wars.